Evidence of association of a 'Candidatus Phytoplasma cynodontis' with bermuda grass (Cynodon dactylon) and 'Candidatus Phytoplasma asteris' with periwinkle (Catharanthus roseus) from western Uttar Pradesh, India. (August 2015) - Khanna, Shivani; Singh, Jitender; Singh, Rupali; Kumar, Pankaj; Rani, Teena; Baranwal, V.K.; Sirohi, Anil; Bertaccini, Assunta
Abstract: Typical symptoms of Phytoplasma like whitening of leaves, phyllody, virescences, yellowing of leaves and little leaves were observed in bermuda grass and periwinkle plants in Meerut district of Uttar Pradesh, India during May–August 2012–13. The presence of phytoplasma was confirmed by amplification of the 16S rDNA gene and SecA gene by phytoplasma specific primers. PCR results with P1/P7 and SecA primers revealed the presence of phytoplasma in 6 and 12 plants out of 10 and 20 symptomatic plants of bermuda grass plants and periwinkle plants, respectively. Sequencing and Phylogenetic analysis of ∼1.25 kb of the 16S rDNA gene and ∼840 bp of non-ribosomal secA gene fragments indicated that the phytoplasma associated with bermuda grass is ' Candidatus Phytoplasma cynodontis' which belongs to the 16SrXIV-A subgroup while the phytoplasma infecting Periwinkle is ' Candidatus Phytoplasma asteris' which belongs to the 16SrI-B subgroup. Highlights: Phytoplasmas were detected in 6 out of 10 Bermuda grass samples, while 12 out of 20 periwinkle plants were positive in PCR. A 16Sr XIV-A group Phytoplasma ' Candidatus Phytoplasma cynodontis' was found to be associated with the bermuda grass. A 16SrI-B group Phytoplasma ' Candidatus Phytoplasma asteris' was associated with periwinkle.